Implementasi Pembelajaran Akidah Akhlak Siswa Kelas V Madrasah Ibtidaiyah Mahad Al-Zaytun - Rusyadi, Rusyadi; Rahim, Abdur (JUPE : Jurnal Pendidikan Mandala, 2023)
This undergraduate thesis investigated the implementation of belief and moral learning of Grade V Students at Madrasah Ibtidaiyah Mahad Al-Zaytun. The focus of this research was to find out the implementation of moral and belief learning of grade V students at Madrasah Ibtidaiyah Mahad Al-Zaytun. The purpose of this research was to find out the implementation of moral and belief learning of grade V students at Madrasah Ibtidaiyah Mahad Al-Zaytun. This research employed qualitative research method with qualitative naturalistic approach and case study design. The source of primary data in this research was the interview result obtained from the teacher of moral and belief of grade V students at Madrasah Ibtidaiyah Mahad Al-Zaytun while the secondary data were obtained from documents of Madrasah Ibtidaiyah Mahad Al-Zaytun. The results of this research concluded that the implementation of moral and belief learning conducted by the teacher at Madrasah Ibtidaiyah Mahad Al-Zaytun has been in line with curriculum 2013 started from introduction, core activity, until closing. In the implementation of moral and belief learning the teacher utilized scientific approach, and in its implementation the teacher used Lesson Plan (RPP) which had been prepared previously. Not only delivering the material in the form of theory, the teacher also directed the students to apply good habits such as when meeting the teacher, friend or anyone in the school environment they must say greeting, act, and behave politely towards teachers and or peer friends. Besides, the students were also required to dress clean and neat at dormitory or at school and being discipline when walking from the dormitory to the learning building.